Penyaringan Cepat dan Toleransi Tanaman Jagung terhadap Intensitas Cahaya Rendah - Syafruddin, Syafruddin; Suwarti, Suwarti; Azrai, M. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Maize cropping under plantation tree crop has a potential for increasing the national maize production. Environment under the tree crops has relatively low light intensity, which hinder the leaf photosynthesis. Therefore, research to identify maize genotypes tolerant to low light intensity was conducted. The research was carried out in three stages; stage-1 was to identify the most effective shading method to be used for the rapid screening, consisted of two treatments, namely: 87.5% and 99.9% light interception. Stage-2 was rapid screening of 160 maize genotypes at germination stage, under the dark room to select tolerance genotypes. The stage-3 was to study physiological mechanism of maize growth under low light intensity stress by planting nine tolerant and susceptible genotypes. The results showed that rapid screening of maize for tolerant to low light intensity stress can be done by growing newly germinating maize for 8 days in the dark room. Genotypes G02 x 7; CY 15 x MAL03; AP.1 x 1042-37; B11 x 265-A; MR12 x MAL04; MR14 x 270C; G02 x 5; AMB07 x CML161 and 1044-9 x 1027-11 were found to be tolerant to low light intensity stress. Growing maize seedling in the dark room had decreased chlorophyll content, carbohydrates and fat, however, the Nitrogen (N) content in the leaves increased. Tolerance genotypes response to low light intensity was indicated by decreasing chlorophyll, carbohydrates and fat content, as well as increasing Nitrogen content, much less than those of susceptible genotypes.